Diagnosis of Angioimmunoblastic T Cell Lymphoma After Receiving First Dose of Pfizer/BioNTech (BNT162b2) Vaccine: A Case Report - Jai Kumar Khatri MD; Ihab Tahboub MD; Khurram Anwar MD; Moh'd Masoudi MD; Vincent Graffeo MD; Muhammad Omer Jamil MD (SAGE Publishing, 2024)
Pfizer/BioNTech (BNT162b2) is a messenger RNA (mRNA) vaccine that is highly effective in preventing the most severe outcomes of COVID-19 infection. Nucleoside-modified severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccines induce effective stimulation of T follicular helper (TFH) cells, leading to a robust germinal center B cell response. Side effects from the BNT162b2 vaccination, including significant lymphadenopathy, have been reported previously. Here, we present a case of angioimmunoblastic lymphoma (AITL), a rare, peripheral T-cell lymphoma with RHOA-G17v-mutated gene developing in a patient following BNT162B2 vaccine with a plausible explanation. A 60-year-old Asian female received her first dose of Pfizer BNT162B2 mRNA vaccine in August 2021. Right after her vaccination, she developed right axillary lymphadenopathy. She received her second vaccine dose in September 2021. Thereafter, she developed lymph node (LN) enlargement in her neck and groin. She underwent left posterior cervical and left groin LN excisional biopsy in April 2022 due to persistent palpable lymphadenopathy. Biopsy results then demonstrated benign follicular hyperplasia. For progressive B symptoms, a right axillary LN biopsy was done, which demonstrated AITL, with molecular studies revealing mutation in TET-2, IDH-2, and RHOA-G17v genes. Progression of AITL following BNT162B2 mRNA vaccine is limited in literature. Our case demonstrates a plausible correlation between the diagnosis of AITL following mRNA vaccination due to the malignant transformation of the TFH cells in patients who have a predisposing mutation of RHOA-17v. Given the rarity of AITL and the heterogeneity of molecular findings, more studies are needed to establish such an association.